Education and entrepreneurs : the future of Malaysian high technology small business - Noraini Abu Talib; Mohd. Hassan Mohd. Osman; Suzilawati Kamarudin; Kamariah Ismail (Skudai : Universiti Teknologi Malaysia)
36